2015
DOI: 10.3171/2014.10.focus14682
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's disease: predicting long-term remission after surgical treatment

Abstract: Cushing's disease (CD) is a state of excess glucocorticoid production resulting from an adrenocorticotropic hormone (ACTH)–secreting pituitary adenoma. The gold-standard treatment for CD is transsphenoidal adenomectomy. In the hands of an experienced neurosurgeon, gross-total resection is possible in the majority of ACTH-secreting pituitary adenomas, with early postoperative remission rates ranging from 67% to 95%. In contrast to the strong data in support of resection, the clinical course of postsurgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 70 publications
(126 reference statements)
2
35
1
1
Order By: Relevance
“…Incorporating feature selection and univariate analysis, some results corroborated the previous studies, suggesting that younger age [43, 44], higher postoperative morning serum cortisol [6, 9-13], and higher postoperative morning ACTH [11, 14, 45, 46] had a detrimental effect on recurrence.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Incorporating feature selection and univariate analysis, some results corroborated the previous studies, suggesting that younger age [43, 44], higher postoperative morning serum cortisol [6, 9-13], and higher postoperative morning ACTH [11, 14, 45, 46] had a detrimental effect on recurrence.…”
Section: Discussionsupporting
confidence: 75%
“…Previously, the postoperative serum cortisol nadir was the common risk factor to predict recurrence after TSS for CD; however, it had poor accuracy according to many studies [8, 11, 15, 41, 42]. We showed that the performance of postoperative morning serum cortisol nadir in predicting CD recurrence was poor (AUC = 0.635) and significantly worse than that of most ML-based predictive models.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations